Sandfly Surveillance within an Emerging Epidemic Focus ofCutaneous Leishmaniasis in Southeastern Iran - MR Yaghoobi-Ershadi; M Hakimiparizi; AR Zahraei-Ramazani; H Abdoli; AA Akhavan; M Aghasi; MH Arandian; AA Ranjbar (Tehran University of Medical Sciences, 2010)
Background: Cutaneous leishmaniasis due to Leishmania major has become a hot topic in Iran. The objective of this study was to determine some ecological aspects of sand flies in the study area. Methods: Sand flies were collected biweekly from indoors and outdoors fixed places in the selected villages, using 30 sticky paper traps from the beginning to the end of the active season of 2006 in Kerman Province, south of Iran. The flies were mounted and identified. Some blood fed and gravid female sand flies of rodent burrows and indoors were dissected and examined microscopically for natural promastigote infection of Leishmania parasite during August to September. Results: In total, 2439 specimens comprising 8 species (3 Phlebotomus and 5 Sergentomyia) were identified. The most common sand fly was P. papatasi and represented 87.1% of sand flies from indoors and 57.2% from outdoors. The activity of the species extended from April to end October. There are two peaks in the density curve of this species, one in June and the second in August. Natural promastigote infection was found in P. papatasi (12.7%). Conclusion: Phlebotomus papatasi is considered as a probable vector among gerbils and to humans with a high percentage of promastigote infection in this new focus of cutaneous leishmaniasis. The Bahraman area which until recently was unknown as an endemic area seems now to represent a focus of zoonotic cutaneous leishmaniasis transmission in Iran.